Bioavailability of Quercetin in Humans with a Focus on Interindividual Variation - Almeida, A Filipa; Borge, Grethe Iren A; Piskula, Mariusz; Tudose, Adriana; Tudoreanu, Liliana; Valentová, Kateřina; Williamson, Gary; Santos, Cláudia N (Comprehensive reviews in food science and food safety, 2018)
After consumption of plant-derived foods or beverages, dietary polyphenols such as quercetin are absorbed in the small intestine and metabolized by the body, or they are subject to catabolism by the gut microbiota followed by absorption of the resulting products by the colon. The resulting compounds are bioavailable, circulate in the blood as conjugates with glucuronide, methyl, or sulfate groups attached, and they are eventually excreted in the urine. In this review, the various conjugates from different intervention studies are summarized and discussed. In addition, the substantial variation between different individuals in the measured quercetin bioavailability parameters is assessed in detail by examining published human intervention studies where sources of quercetin have been consumed in the form of food, beverages, or supplements. It is apparent that most reported studies have examined quercetin and/or metabolites in urine and plasma from a relatively small number of volunteers. Despite this limitation, it is evident that there is less interindividual variation in metabolites which are derived from absorption in the small intestine compared to catabolites derived from the action of microbiota in the colon. There is also some evidence that a high absorber of intact quercetin conjugates could be a low absorber of microbiota-catalyzed phenolics, and vice versa. From the studies reported so far, the reasons or causes of the interindividual differences are not clear, but, based on the known metabolic pathways, it is predicted that dietary history, genetic polymorphisms, and variations in gut microbiota metabolism would play significant roles. In conclusion, quercetin bioavailability is subject to substantial variation between individuals, and further work is required to establish if this contributes to interindividual differences in biological responses.
Keywords: quercetin; ADME; metabolism; interindividual